COVID-19 IMPACT ON DEBT CHOICES OF HEALTHCARE COMPANIES: EVIDENCE FROM INDONESIA - Lukman, Cecilia Jelsica; Muttaqin, Aminnulah Achmad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The COVID-19 pandemic, caused by the SARS-CoV-2 virus, has had a huge global impact since its emergence in December 2019. This research explores the various impacts of the pandemic on the Indonesian economy, with a particular focus on the healthcare sector from 2019 to 2022. This research aims to determine the impact of COVID-19 on debt choices in the health sector listed on the IDX. The research timeline encompasses the years 2019 through 2022, designating the period from 2019 to 2021 as the active COVID-19 timeframe, with 2022 denoted as a post-COVID-19 phase. Debt choice is represented by the debt-to-equity ratio (DER). Then, this research uses panel data, which is secondary data. This research uses Repeated Measure ANCOVA, which is regressed using the STATA 14.2 application. This research concludes that the COVID-19 pandemic affects the debt choices of healthcare companies. The findings support the idea that the pandemic has a marked impact on the debt choices of healthcare firms in Indonesia, emphasizing the need for adaptability in financial strategies during times of significant global disruption.